2005 IEEE Engineering in Medicine and Biology 27th Annual Conference 2005
DOI: 10.1109/iembs.2005.1617105
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Bioelectric Currents Based on the Coupling of Electric and Magnetic Field

Abstract: A method based on magneto-acoustic technique is developed to measure bioelectric currents non-invasively. Theoretically, vibrations of particles in the medium are produced due to the Lorentz force when oscillatory currents flow through medium in a steady magnetic field. These vibrations contain information of the bioelectric currents and can be detected by surface contact detector. An experimental setup is presented to detect the microampere level currents in saline and tissue. The results show the linear rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…In theory, the induced electric field is consistent with the focused ultrasonic field in a homogeneous medium. In 2006, Zhang et al (Hongmiao et al, 2005) tested Norton's theoretical format. They analyzed the electrical signals in a gel saline phantom resulting from a combination of ultrasonic signals and static magnetic field and found that the electrical signals were consistent with the ultrasonic signals in the frequency domain.…”
Section: Introductionmentioning
confidence: 99%
“…In theory, the induced electric field is consistent with the focused ultrasonic field in a homogeneous medium. In 2006, Zhang et al (Hongmiao et al, 2005) tested Norton's theoretical format. They analyzed the electrical signals in a gel saline phantom resulting from a combination of ultrasonic signals and static magnetic field and found that the electrical signals were consistent with the ultrasonic signals in the frequency domain.…”
Section: Introductionmentioning
confidence: 99%